The Readiness Of The Administrators And Undergraduates In Using Massive Open Online Course (MOOC) In The Mandarin Subject - Cheong, Kar Mee; Khoo, Linda Mei Sui; Jano, Zanariah; Hussin, Hanipah (Medwell Journals, 2016)
This study, embarked on the following objectives: to investigate Mandarin MOOC administrators’ readiness for the planning and implementation of Mandarin MOOC; to find out undergraduate’s opinion on the effectiveness of the online learning or MOOC and to examine the critical factors for the sustainability of Mandarin MOOC from the perspective of Mandarin MOOC administrators and under graduates. This is a qualitative study using an in-depth face-to-face interview. A Single Case Single issue (SCSS) was also used. The findings yielded that internet connection affected the engagement of learners in online learning. Besides, another challenge in sustaining Mandarin MOOC is the quality of Mandarin MOOC content. Among the strategies to sustain Mandarin MOOC are through creating usable content for MOOC and improving the internet connection. This study, is beneficial for stakeholders in MOOC including tutors, policy makers and administrators. In future, more studies should be done to evaluate whether this course can address the needs of the diverse population.